The Eighth Industrial Fluids Properties Simulation Challenge - Nathan E Schultz; Riaz Ahmad; John K Brennan; Kevin A Frankel; Jonathan D Moore; Joshua D Moore; Raymond D Mountain; Richard B Ross; Matthias Thommes; Vincent K Shen; Daniel W Siderius; Kenneth D Smith (Adsorption Science & Technology)
The goal of the eighth industrial fluid properties simulation challenge was to test the ability of molecular simulation methods to predict the adsorption of organic adsorbates in activated carbon materials. In particular, the eighth challenge focused on the adsorption of perfluorohexane in the activated carbon BAM-P109. Entrants were challenged to predict the adsorption in the carbon at 273 K and relative pressures of 0.1, 0.3, and 0.6. The predictions were judged by comparison with a benchmark set of experimentally determined values. Overall, good agreement and consistency were found between the predictions of most entrants.